دراسة أحد تطبيقات مسائل النمذجة الرياضيَّة العشوائيَّة (Latakia University Journal -Basic Sciences Series, 2014)
الغاية من هذا البحث هو دراسة وإنشاء أنموذج رياضي عشوائي ضمن شروط احتمالية مفروضة, وتحديداً بناء أنموذج عشوائي لمجمّع طاقة شمسية خاص بإزالة الملوحة من الماء, وبالتالي الحصول على الماء العذب, وذلك ضمن شروط محددة. نؤكد أن مسألة إيجاد القيم المثلى لمتغيرات المجمّع الشمسي أعلاه تمثل صنفاً خاصاً من مسائل النمذجة الرياضية العشوائية – اللاخطية , ونشير إلى أن الطرق الأكثر فعالية لإيجاد الحلّ الأمثل لمثل هذا النوع من المسائل هي الطرق العشوائية شبه المتدرجة.   The purpose of this research is to study and create a mathematical model under the terms of the probability of randomly imposed, specially by building a model of random Complex Solar particular by removing the salinity of the water, and thus to obtain fresh water and that, under certain conditions. We  Assure  that the question of finding the optimum values ​​for the variables solar collector above represent varieties of special issues of mathematical modeling and nonlinear stochastic, we point to that  the most effective ways to find the perfect solution for this kind of issues are stochastic gradient methods.